The Role Of “Il 10 (-2 1082 A/G)” Promoter Polymorphism In Ovarian Epithelial Cancer Pathogenesis - Siti Fatimah; Rika Hairunisyah (Yayasan Rumah Ilmu Professor, 2022)
Ovarian cancer (ovarian cancer) is the abnormal development of cells in one or two ovaries. Many cytokine functions are related to the development of immunological and inflammatory responses that play essential roles in cancer pathogenesis. Among the cytokines, interleukin 10 (IL-10) is an anti-inflammatory cytokine involved in the downregulation of cytotoxic and inflammatory cell-mediated responses. This study aims to determine the relationship between the Gene Promoter Polymorphism Interleukin 10 (-1082 A/G) with the incidence of ovarian epithelial cancer. This research is an observational analytical study conducted at the Molecular Biology Laboratory in Palembang City in October-December 2021. The number of samples was 60 respondents consisting of 30 case groups and 30 control groups. Data were obtained by genotype and allele using PCR-RFLP, which was then analyzed by Chi-Square test to determine whether there was a relationship. The results showed no significant relationship between the promoter of the IL 10 gene polymorphism (-1082 A/G) and the incidence of ovarian epithelial cancer.